Research Review of Ratan Hindi’s Claim of the Companionship of Prophet (PBUH) - Muhammad Saeed Shafiq; Zia, Miraj ul Islam (Journal of Islamic and Religious Studies, 2016)
Ratan Hindi was born in the Indian side of the Punjab in the 6th AH. He claimed that he had met Prophet Muḥammad (PBUH) in Madinah; had accepted Islam in his presence; joined the wedding ceremony of Fatimah (RA) and had also took part in the battle of trench (Ghazwah-e-Khandaq). He also affirmed that his long age was due to the blessings of the Prophet (PBUH) who prayed for his long life. It is also said that he had witnessed the miracle of the splitting of moon in India. The present paper, after proper investigation conducted in the light of original sources, i.e. Ḥadith and its Sciences, books of Rijal and history of Islam prove his claim of Ṣahabiyyat to be false and baseless. It also presents definition of a Ṣahabi (Prophet’s Companion) along with conditions deemed by scholars of Ḥadith for such a position.